(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In this article the author tries to justify the idea that in the history of philosophy it is necessary to restore the status of relativism as a special form of philosophizing and philosophical way of thinking. The main idea of the author is striving to show that relativism is not merely a marginal type of philosophical thinking, but in a certain way of strategy in the cultural life of the people, by inﬂ uencing the understanding of connection between man and nature, culture and nature, civilization and the human relationship to it. Based on the idea that the Western version of relativism has a place in history, the author considers his research to justify the possibility of relativism in the eastern culture. The author believes that the allocation of relativism as a special type of thinking and cultural strategy in the eastern culture is necessary. According to the author, the rationale for the possibility of the eastern variant of relativism to help overcome certain absolute of dialectics, in which many forms of Eastern relativism regarded as one of the historical forms of dialectics. To rebut the common idea of absolute dialectics as a doctrine of development in world history of philosophy, the author tries to show that the desire to ﬁ nd the causes of the marginalization of relativism as a special type of philosophizing, as in the West and in the East has its own speciﬁ c goals and objectives. In this article the author puts forward a number of abstracts, which are necessary for him to enter the research problem of the possibility of relativism in the Eastern culture and history of philosophy. Expanding the number of features of the eastern version of relativism, the author seeks to show the importance of further study of this complex and historical-philosophical problem.